2015
DOI: 10.3168/jds.2015-9738
|View full text |Cite
|
Sign up to set email alerts
|

Cupuassu (Theobroma grandiflorum) pulp, probiotic, and prebiotic: Influence on color, apparent viscosity, and texture of goat milk yogurts

Abstract: Cupuassu is an acidic fruit that has a characteristic aroma, flavor, and texture; its fiber-rich pulp can provide a different consistency than other fruit pulps. Goat milk is an excellent source of amino acids, fatty acids, and minerals, and is widely used for processing fermented milks, such as yogurt. However, compared with cow milk yogurts, it is difficult to make goat milk yogurts with a good consistency. Therefore, it is necessary to use certain technological strategies. This study was carried out to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 46 publications
(54 reference statements)
12
69
1
7
Order By: Relevance
“…Cohesiveness is also one of the important parameters to define the texture of yogurt as it assesses the quality of yogurt that a force is required to prevent the yogurt adhered to the spoon or mouth when eating the product (Costa et al, 2015). So, 2% EFSP could be the optimal concentration that provides an accurate effect of viscosity building capacity of soluble components and water binding.…”
Section: Discussionmentioning
confidence: 99%
“…Cohesiveness is also one of the important parameters to define the texture of yogurt as it assesses the quality of yogurt that a force is required to prevent the yogurt adhered to the spoon or mouth when eating the product (Costa et al, 2015). So, 2% EFSP could be the optimal concentration that provides an accurate effect of viscosity building capacity of soluble components and water binding.…”
Section: Discussionmentioning
confidence: 99%
“…In general, inulin is a water‐soluble fibre and it was observed to form complexes with proteins of goat milk leading to a part of a strong structural network (Costa et al . ). Similarly, De Souza Oliveira et al .…”
Section: Resultsmentioning
confidence: 97%
“…In the kefir samples, the increased a * and decreased b * values indicated that the reddish colour was reinforced, which may be attributed to lipid oxidation (Costa et al . ).…”
Section: Resultsmentioning
confidence: 97%